Kajian Teologi Misi Terhadap Persembahan Di Jemaat GMIM Alfa Omega Rinegetan Wilayah Tondano II - Mantiri, Syalomitha Fabiola; Sarimbangun, Ramli (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This article aims to conduct an in-depth study of Offerings in the Alfa Omega Rinegetan congregation in the perspective of Mission Theology. Offerings are a form of gratitude from believers and the offerings given by these believers are collected to support the work of church ministry which is part of the implementation of God's Mission in this world. So giving meaningful offerings is one of the ways as a believer to help in the service of God's mission through the church. However, the reality that occurs in the GMIM Alfa Omega Rinegetan congregation is the lack of understanding and meaning of the congregation to give offerings, which also affects the way they give. And in this study, the author uses qualitative research methods. The results of this research will explain the understanding of the congregation and the responsibility as believers in giving offerings in order to help the work of God's mission in this world through the church. The end of this paper is a conclusion that confirms the answer to the purpose of the research.